(untitled) (Journal of the College of Basic Education, 2024)
The current research aims to identify the effect of the Damage to Dispersion strategy to develop achievement motivation and performance skills among students of the Art Education Department in post-modern arts for the project subject. The research objective is achieved through. 1- Building study plans according to the Damaged Dispersion strategy. 2- Measuring the size of the impact of the study plans by testing them on a sample of students from the Art Education Department. . The total sample of the research was (60) male and female students distributed into two groups: experimental (30) and control (30). To achieve the goal of the research, the researcher used the experimental method and experimental design with two groups. The researcher prepared the research tool represented by the achievement motivation scale, which consists of (20) items, and it was characterized by honesty. And stability, and the experiment lasted (9) weeks. After applying the tool and using statistical methods to process the data, the results showed that there was a statistically significant difference between the average grades in favor of the students of the experimental group taught using the strategy of destroying distractions over the control group that taught according to the usual method for the project subject in arts. Postmodernism at a significance level of (0.05) in the post-test of the achievement motivation scale. . Through the research results, the researcher presented a number of recommendations and proposals. Among them is relying on the study plans that were designed in the current research in relevant institutions such as (faculties of basic education, colleges of fine arts, and institutes of fine arts), in which the project material on the subject of post-modern arts is taught to prove its efficiency, impact, and ability to develop students’ skills.